[Proximal protection systems using carotid artery stent] - Grunwald, I; Dorenbeck, U; Axmann, C; Roth, C; Struffert, T; Reith, W (2004)
Controversies as to whether or not a protection device should be used in carotid artery stenting exist. Currently three temporary cerebral protection devices are being used. These are devices with distal balloon occlusion or filtration baskets and proximal occlusion devices with flow reversal in the internal carotid artery. This article focuses on flow reversal systems and aims to give some advice as to which patients could benefit from their use.